POSTPARTUM DEPRESSION AND THE RISK OF STUNTING AMONG CHILDREN IN INDONESIA: A LITERATURE REVIEW - Al Ilham Ksatria Gagah Perkasa Perkasa; Jessica Reitanya Putri; Nibras Azeenshia Winarno; Bunga Pelangi; Salma Dhiya Rachmadani (PT. Varians Statistik Kesehatan, 2026)
Background: Postpartum depression was found to be linked to disrupted growth development patterns, particularly stunting. In Indonesia, challenges are found in correlating the two variables due to the lack of official data. The findings of this review may provide valuable initiatives for further research and intervention on maternal mental well-being. Objective: This study aims to review the correlation between postpartum depression and the risk of stunting, alongside the trends in Indonesia; and how it is compared with the global context. Method: We searched PubMed, Scopus, Taylor and Francis, and Google Scholar (2016-2026) for cross-sectional studies, cohort studies, systematic reviews, and meta-analyses examining the correlation between postpartum depression and stunting within a global and local context, alongside challenges faced by the healthcare system regarding postpartum depression. Results: Despite the lack of official data on postpartum depression, we found studies that examined positive correlations between depression and the risk of stunting in Indonesia. A higher risk of stunted children was found in mothers with postpartum depression. Several challenges in the Indonesian healthcare system were also found, these consist of lack of focus on mental health indicators, stigmatization of mental illnesses especially in mothers, a lack of access to maternal mental health care, and the limited training provided to healthcare workers on maternal mental health. Conclusion: Despite consistent evidence from multiple studies, Indonesia still faces major gaps in data, awareness, and mental health services for mothers; gaps that are worsened by stigmatization, and prioritization of physical over psychological healthcare. Integration of maternal mental health screening and support into existing mother-child health programs is recommended to mitigate stunting and improve child development outcomes.